Appena un po’ meno umane. Sulle strategie di deumanizzazione nei confronti delle donne - Corio, Serena; Di Porto, Ketty (Il sogno della farfalla, 2020)
The authors of this article deal with the topic of inhumanity which has been at the core of an educational project by themselves carried out in collaboration with other experts. This paper considers the knowledge acquired on this topic by discussing Fagioli’s Human birth theory and in particular the concept of annulment pulsion in relation to the psychosocial research on dehumanization carried out by Chiara Volpato in Italy. By looking at the female condition, the article examines the different forms of blatant and subtle dehumanization, underlining the need for a dialogue between psychosocial research and psychopathological and psychodynamic research on the topics of inhumanity and human identity.